Pandemic response : role of the state - Farrow, Luca (2020)
The COVID-19 pandemic has bolstered the case for large-scale government intervention in the economy and in ensuring social welfare. It has thrown into further doubt the neoliberal notion that shrinking the public sector to empower the private market will deliver optimal social and economic outcomes.